2019
DOI: 10.1302/0301-620x.101b11.bjj-2019-0480.r2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of Vancouver type B periprosthetic femoral fractures

Abstract: Aims We investigated patient characteristics and outcomes of Vancouver type B periprosthetic fractures treated with femoral component revision and/or osteosynthesis. Patients and Methods The study utilized data from the Swedish Hip Arthroplasty Register (SHAR) and information from patient records. We included all primary total hip arthroplasties (THAs) performed in Sweden since 1979, and undergoing further surgery due to Vancouver type B periprosthetic femoral fracture between 2001 and 2011. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…This preference is a clear example of discrepancy between surgeons opinions and current evidence because the same authors made a systematic review where they found a higher rate of nonunion and increased risk of hardware failure by using locking plate alone instead of cable plate. 15 …”
Section: Discussionmentioning
confidence: 99%
“…This preference is a clear example of discrepancy between surgeons opinions and current evidence because the same authors made a systematic review where they found a higher rate of nonunion and increased risk of hardware failure by using locking plate alone instead of cable plate. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PFFs depends on 5 important factors: level of fracture, stability of the implant and of the fracture, quality and quantity of bone stock, patient’s factors (as age, comorbidities and functional demands), and surgeon experience. 2 , 10 , 22 , 31 - 33 The aim of this review is to describe state-of-the-art treatment in the management of PFFs, and to propose a summary to guide treatment choice.…”
Section: Introductionmentioning
confidence: 99%
“…The true incidence of PFF remains unknown, but a prevalence of 0.1–4% has previously been estimated [ 3 , 7 – 9 ]. National joint registries, except the Swedish Hip Arthroplasty Registry, record only those PFFs which necessitate revision, failing to capture those managed non-operatively or by ORIF [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%